PENGARUH VARIASI JUMLAH SUDU TERHADAP DAYA OUTPUT PADA PROTOTYPE PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) DENGAN MENGGUNAKAN TURBIN CROSSFLOW - Andi Dinata, Putu; Arta Wijaya, I Wayan; Suartika, I Made (Jurnal SPEKTRUM; Vol 7 No 3 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i03.p5, 2020)
Crossflow turbine is a type of turbine that often used as a prime mover in MHP system. this type of turbine has an advantage witch can be applied in low head with high water discharge. The output power from this turbine is effected by the number of blades that installed on the tubine runner. The aim of this study is to hold an experimental study of the number of blade that used on crossflow turbine to get the maximum output power. The number of blade that used is 10, 14, 18, 22, and 26 blades. Where from the result of calculations, it is found that turbine with number of blades 18 has the higest efficiency with a value of 8,52%.